KONSEP DRAVYA YADNYA DALAM BHAGAVAD GITA - Ni Luh Komang Indah Sari (Pangkaja: Jurnal Agama Hindu, 2022)
This article explores the hidden Bhagavadgita and no one knows about material offerings to all living beings. This Bhagavadgita appears as a light of knowledge for humans so that humans can have a sense of concern for fellow humans through offerings or sacrifices. Offerings that are easily accessible and performed consistently are called Dravya Yadnya. The concept of Dravya Yadnya is a depiction of human life that is carried out by making sacrifices or offerings in the form of Punia or alms. This act is done so that all beings can live in prosperity through their caring attitude. This study aims to provide the life of every human being through devotional service or offerings in the form of material or non-material that can be beneficial for all human life. This research is qualitative research with a qualitative descriptive analysis method using data collection, such as literature (library) and several references that can support this research. Based on the results of the research, Dravya Yadnya is one of the core Yadnya or the concept of the holy sacrifice that can be given to all human beings in the form of material and non-material sincerely and selflessly.